COLLABORATIVE GOVERNANCE DALAM PENGELOLAAN PULAU TERLUAR STRATEGIS NASIONAL UNTUK MENDUKUNG PERTAHANAN MARITIM - Abdillah, Isna Muhsin; Tjenreng, Muhammad Baharuddin Zubakhrum (Program Studi Ilmu Pemerintahan FISIP Universitas Galuh, 2025)
Indonesia, the largest archipelagic country in the world, has more than 17,000 islands, including outer islands that play a strategic role in national maritime defense. However, managing these islands faces challenges such as limited infrastructure, human resources, security threats, and suboptimal coordination between institutions. This study analyzes the application of Collaborative Governance in managing strategic islands to support national maritime defense, using a qualitative descriptive approach and case study method. Data were obtained through interviews, field observations, and policy document analysis. The findings show that local governments play a role in infrastructure development, while the Marine Corps/Navy ensures security and provides education to the community. However, collaboration is still hindered by differences in priorities, ineffective communication, and limited human and financial resources. Effective implementation of Collaborative Governance requires strategic coordination through joint teams, increased coordination meetings, and community involvement in managing marine resources. Strengthening security capacity through the provision of modern equipment and harmonizing policies between central government, local governments, and the military are crucial factors. This study emphasizes that the synergy between local governments and the Marine Corps/Navy in Collaborative Governance can enhance the effectiveness of managing strategic islands, support maritime defense, and contribute to community welfare and Indonesia's world maritime axis policy.